Peran geostrategi dalam kehidupan bernegara - Mubarak, Muhammad Rafid (Maliki Interdisciplinary Journal, 2026)
This study discusses the role of geostrategy in state governance, emphasizing the relationship between a country’s geographical conditions and its national strategies in politics, economy, defense, and development. Geostrategy is understood as an essential approach used by states to utilize their geographical location, natural resources, and strategic territorial position in order to achieve national goals and maintain sovereignty. The main issue addressed is the suboptimal utilization of geostrategic potential in many countries, including Indonesia, as indicated by regional development disparities, weak border control, and increasing non-traditional threats such as transnational crime and cyberattacks. The discussion shows that geostrategy plays a crucial role in strengthening national resilience through strategic territorial management, defense system enhancement, and equitable development. Geostrategy also contributes to improving national competitiveness at the global level by leveraging strategic geographic positions in international trade and cooperation. In conclusion, geostrategy is a fundamental instrument in state governance that not only focuses on security aspects but also includes sustainable development and public welfare. Therefore, the integration of geostrategic considerations into national policies is essential to ensure that territorial potentials are optimally utilized for national interests.